UPAYA MENINGKATKAN KEMAMPUAN GURU DALAM MENULIS ARTIKEL MELALUI IN HOUSE TRAINING DI SD NEGERI 3 PEGUYANGAN - Ni Wayan Darti (LP3M Universitas PGRI Mahadewa Indonesia, 2022)
This study aims to improve the ability of teachers to write articles at SD Negeri 3 Peguyangan in the second semester of the 2020/2021 academic year. This research is based on the number of teachers who have not mastered how to write articles and the number of teachers who have never written. The author holds activities for teachers to improve their ability to write articles that are packaged in In House Training activities. Through this activity, it is hoped that it will improve the ability of teachers to write articles at SD Negeri 3 Peguyangan. This study involved 1 resource person and 12 teachers as participants. In House Training activities take place from January to June 2021 in two cycles. The results showed that In House Training activities have been able to improve the ability of teachers in writing articles to obtain a very high category in terms of the teacher's ability to write articles and the category is very high when viewed from the effectiveness of In House Training activities. In House Training activities really need to be developed in schools as a forum to improve teacher professionalism, especially in the field of writing articles. This is because the theme and time can be flexible according to the needs of the school. Competent resource persons are sought to be able to transmit their abilities to teachers at school.